Enhanced Organizational Performance: Integrating Dimensions for Sustainable Growth - Restrepo-Morales, Jorge Aníbal; Giraldo-Betancur, Emerson Andrés; López-Cadavid, Diego Alejandro; Grados-Vásquez, Martín Manuel; Olórtiga-Cóndor, Lucio Wilfredo (Sustainability, 2023)
This study examined how different factors—environmental, human resources, managerial, technological, and innovation—influence the organizational performance of small- and medium-sized enterprises (SMEs). For the study methodology, a correlational research design was used to examine the relationships between variables in a sample of 476 SMEs in Colombia. Advanced statistical techniques were used, such as regression and correlation analyses with Monte Carlo simulation. We evaluated four dimensions, 16 factors, and 197 related variables to understand their impact on business performance. The results show that all the studied factors, i.e., environment, structure, management, and people, have a positive relationship with organizational performance. Additionally, the results indicate that SMEs tend to have strong performance in the dimensions of finance, infrastructure, and production but weaker performance in those of international, socioenvironmental, technological, institutional philosophy, process, and human resources management. These findings provide valuable insight into the areas that SMEs may need to focus on to improve their performance while underscoring the importance of considering a variety of factors when developing strategies to improve organizational performance.